A study on the growth and physiological traits of Leymus chinensis in artificial grasslands under exogenous hormone regulation - Jifu Chen; Qiang Chen; Xiangyang Hou (Scientific Reports)
Abstract Leymus chinensis is a dominant perennial grass species in the Eurasian steppe, valued for its ecological and economic importance. Conducting research on the formation mechanism and regulatory approaches of artificial grassland productivity is the great significance for improving grassland productivity, and restoration and reconstruction of degraded grassland. Select three-year-old sheep grassland as the experimental field, diethyl aminoethyl hexanoate (DA-6), brassinolide (BR), and melatonin (MT) were sprayed to explore the regulatory mechanisms and differential efficacy of different phytohormones on grassland productivity. MT promotes chlorophyll synthesis, drives enhanced photosynthesis and protein synthesis, DA-6 upregulated photochemical efficiency and improves the stability of light energy conversion. BR enhances water use efficiency (WUE) through synergistic effects of pore regulation. MT demonstrated significant in the accumulation of biomass during the early and middle growth stages, and upgrade the nutritional quality of forage. DA-6 is suitable for biomass accumulation in the later growth stage. BR has outstanding potential in water conservation and stress resistance capacity. This study elucidates the differences in the regulatory effects of different growth regulators on the productivity of sheep pastures, in order to providing technical insights to optimize the technical strategy for grassland restoration and mitigate the contradiction between the degradation of natural grasslands and the development of animal husbandry.